Associations of interactions between NLRP3 SNPs and HLA mismatch with acute and extensive chronic graft-versus-host diseases. Issue 1 (December 2017) - Takahashi, Hidekazu; Okayama, Naoko; Yamaguchi, Natsu; Miyahara, Yuta; Morishima, Yasuo; Suehiro, Yutaka; Yamasaki, Takahiro; Tamada, Koji; Takahashi, Satoshi; Tojo, Arinobu; Asano, Shigetaka; Tanabe, Tsuyoshi
Abstract HLA matching is a well-known genetic requirement for successful bone marrow transplantation (BMT). However, the importance of non-HLA single-nucleotide polymorphisms (SNPs) remains poorly understood. The NLR family pyrin domain–containing 3 (NLRP3 ) inflammasome, a key regulator of innate immunity, is associated with multiple diseases. We retrospectively genotyped SNPs ofNLRP1–3 and caspase recruitment domain family member 8 (CARD8 ), which are implicated in the interleukin 1β (IL-1β) signaling, in 999 unrelated BMT donor–recipient pairs. We identified an association of the interaction between the recipientNLRP3 SNP CC genotype and total HLA mismatches with grade 2–4 acute graft-versus-host disease (AGVHD), and an association of the interaction between the donorNLRP3 SNP T allele and HLA-C mismatch with extensive chronic GVHD (ECGVHD), in both adjusted and unadjusted regressions (P < 0.005). Importantly, the ECGVHD risk associated with HLA-C mismatch was not elevated when the donorNLRP3 genotype was CC. We also identified an association of the interaction between recipientNLRP3 SNP and donor cytomegalovirus seropositivity with overall survival in adjusted regressions (P < 0.005). These results suggest the importance of certain SNP–covariate interactions in unrelated BMT. The three identified interactions may be useful for donor selection or outcome prediction.